Real-time motion and main magnetic field correction in MR spectroscopy using an EPI volumetric navigator - Hess, Aaron T (Department of Human Biology, 2015)
In population groups where subjects do not lie still during Magnetic Resonance Spectroscopy (MRS) scans, real-time volume of interest (VOI), frequency, and main magnetic field (B0) shim correction may be necessary. This work demonstrates firstly that head movement causes significant B0 disruption in both single voxel spectroscopy and spectroscopic imaging.